ANALISIS PROFIL ALAT EVALUASI SISWA BUATAN GURU BIOLOGI - JANEKA KURNIAWATI, SUKMA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
This research aimed to know profile student evaluation instrument made by certified teacher of biology in state high school at Madiun regency. Population and sample were teachers of biology as many 18 teachers. Data collecting technique conducted by documentation study and teacher self assessment questionnaire. Profile of evaluation instrument formulated by teachers was 72.22% in test and 27.78% non test. Types of test were multiple choice 76.02% and limited essay 23.98%. Types of non test were assessment in attitude 54.12%, performance 29.41%, presentation 5.88%, classroom discussion 9.41%, and project assessment 1.18%. Keywords: evaluation instrument, biology teacher, Madiun regency.